Multidisciplinary treatment of a case of temporomandibuolar joint ankylosis (Research, Society and Development, 2022)
Temporomandibular joint ankylosis is a serious disease, characterized by the fusion between the condyle and the mandibular fossa, resulting in constriction of the mandible, due to bone or fibrotic tissue adhesion of the anatomical components. It causes limitation in joint motion range, resulting in significant functional limitations. The aim of this article is to describe the treatment techniques and multidisciplinary care in the functions and quality of life of a patient with temporomandibular joint ankylosis who underwent reconstruction with a costochondral graft. This is a case of left temporomandibular joint ankylosis, which evolved with bone graft resorption, retrognathia, facial asymmetry, and significant functional changes. Although there was a regression in mouth opening and facial asymmetry due to graft resorption, which is indicative of a new arthroplasty and complementary procedures to resolve the case, the multidisciplinary treatment used was effective in improving pain and nutrition. The multiprofessional treatment applied was effective in improving pain and eating. Nevertheless, there was regression in mouth opening and facial asymmetry due to graft resorption, and a new arthroplasty and additional procedures were proposed for improvement of the case.